Problems of diagnosis and treatment of primary operable breast cancer - E. A. Troshenkov; A. A. Kostin (Исследования и практика в медицине)
Cancer breast cancer is a heterogeneous disease with genotypic and phenotypic variability. Phenotypic diversity of tumors is directly related to genotypic variations, which can be determined with analyzing gene expression in a comprehensive immunohistochemical study. Today there are many methods of surgical treatment – from minimally invasive to radical, variable according to the number of stages, the volume of reconstructive techniques. Today organ-preserving operations are prefered by surgeons all the world.